On the design of new europium heteroaromatic carboxylates for OLED application. (November 2019) - Koshelev, Daniil S.; Chikineva, Tatyana Yu; Kozhevnikova (Khudoleeva), Vladislava Yu; Medvedko, Alexey V.; Vashchenko, Andrey A.; Goloveshkin, Alexander S.; Tsymbarenko, Dmitry M.; Averin, Alexey A.; Meschkov, Anna; Schepers, Ute; Vatsadze, Sergey Z.; Utochnikova, Valentina V.
Abstract: The approach to the directed synthesis of lanthanide aromatic carboxylates – precursors to the electroluminescent materials, - was proposed, namely the conjugation length increase and heteroatom introduction in the appropriate position in combination with the neutral ligand introduction. This resulted in the isolation of a series of new lanthanide complexes, among which the highest electroluminescence efficiency was obtained for mixed-ligand europium benzothiazole-2-carboxylate with bathophenanthroline in a solution-processed OLED. The peculiarities of energy transfer processes allowed obtaining luminescence thermometer materials based on this system, which demontrated the sensitivity of 2.8%/K in the physiological range. Graphical abstract: Image 1 Highlights: New benzoxazolates and benzothiazolates of some lanthanides were obtained. Complex properties are mainly independent on the second (O or S) heteroatom nature. Mixed-ligand europium benzothiazolate with batophenanthroline was successfully used in solution-based OLED. Bimetallic terbium-europium benzothiazolate demonstrates temperature-dependent luminescence with high sensitivity (2.8%/K).